2007
DOI: 10.1002/icd.507
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' parenting hassles and coping: associations with emotional expressiveness and their sons' socioemotional competence

Abstract: The present study examined fathers' daily parenting hassles and coping strategies to (a) determine their association with fathers' emotional expressiveness and (b) predict their sons' development of socioemotional competence. Fathers of 148 preschool‐aged boys reported on their parenting hassles, coping strategies, and emotional expressiveness; mothers also reported on fathers' emotional expressiveness; and teachers reported on boys' socioemotional competence. Parenting hassles were associated with less ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Compared with the control participants, the mothers who had received such affirmation behaved more positively toward their children, who in turn were more enthusiastic, showed a higher rate of positive affect in the interaction, and were less irritated in frustrating tasks. Positive emotions elicited by supportive parenting have also been found to promote cognitive abilities such as problem solving (Leerkes, Blankson, O'Brien, Calkins, & Marcovitch, 2011;Otsui & Tanaka-Matsumi, 2007;Park & Woo, 1997;Russ & Kaugars, 2001) and stress coping strategies (Foster, Reese-Weber, & Kahn, 2007;Gentzler, Contreras-Grau, Kerns, & Weimer, 2005;Zimmer-Gembeck, Lees, & Skinner, 2011), both of which are thought to be involved in attentional and behavioral regulation skills (Eisenberg et al, 2005;Leerkes, Blankson, O'Brien, Calkins, & Marcovitch, 2011;Otsui & Tanaka-Matsumi, 2007;Park & Woo, 1997;Russ & Kaugars, 2001). Finally, it has been suggested that support affects the quality of parent-child relationships, in particular the security of attachment (Roskam, Stievenart, Van de Moortele, & Meunier, 2011), which in turn is related to better emotional and behavioral regulation (Lay, Waters, Posada, & Ridgeway, 1995;Panfile & Laible, 2012;Smith, Calkins, & Keane, 2006).…”
Section: Parenting and The Development Of Efmentioning
confidence: 99%
“…Compared with the control participants, the mothers who had received such affirmation behaved more positively toward their children, who in turn were more enthusiastic, showed a higher rate of positive affect in the interaction, and were less irritated in frustrating tasks. Positive emotions elicited by supportive parenting have also been found to promote cognitive abilities such as problem solving (Leerkes, Blankson, O'Brien, Calkins, & Marcovitch, 2011;Otsui & Tanaka-Matsumi, 2007;Park & Woo, 1997;Russ & Kaugars, 2001) and stress coping strategies (Foster, Reese-Weber, & Kahn, 2007;Gentzler, Contreras-Grau, Kerns, & Weimer, 2005;Zimmer-Gembeck, Lees, & Skinner, 2011), both of which are thought to be involved in attentional and behavioral regulation skills (Eisenberg et al, 2005;Leerkes, Blankson, O'Brien, Calkins, & Marcovitch, 2011;Otsui & Tanaka-Matsumi, 2007;Park & Woo, 1997;Russ & Kaugars, 2001). Finally, it has been suggested that support affects the quality of parent-child relationships, in particular the security of attachment (Roskam, Stievenart, Van de Moortele, & Meunier, 2011), which in turn is related to better emotional and behavioral regulation (Lay, Waters, Posada, & Ridgeway, 1995;Panfile & Laible, 2012;Smith, Calkins, & Keane, 2006).…”
Section: Parenting and The Development Of Efmentioning
confidence: 99%
“…Runyon and Deblinger (2013) [35] and Foster et al (2007) [34] believed that parent-child interaction and prosocial behavior were positively correlated. However, those studies may ignore gratitude's mediating effect.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Herschell et al (2003) [27] also supported that parent-child interactions affect prosocial behavior. Foster, Reese-Weber, and Kahn (2007) [34] believed that the demonstration of prosocial behavior by parents in their interactions with their children contributes to the development of this behavior by their children. Runyon and Deblinger (2013) [35]proposed that parents are the models for prosocial behavior, which is established through parent-child interactions.…”
Section: Parent-child Interaction Affects Prosocial Behaviormentioning
confidence: 99%
“…Aligned with these findings, increased relationship quality in mother-child relationships is predictive of greater coping efficacy and active coping in children (Velez, Wolchik, Tein, & Sandler, 2011), while lack of attachment and perceived parental rejection is related to an elevated risk of nonproductive coping styles (Bamberg, Toumbourou, Blyth, & Forer, 2001;Meesters & Muris, 2004, respectively). Fathers' coping strategies have been found to exert an influence on child coping, with father coping strategies predictive of their sons' aggression levels at school (Foster, Reese-Weber, & Kahn, 2007). The main avenues through which parents appear to have an effect on their children's coping include parent modelling of coping strategies, as well as the language used to give insight into their emotional experiences and coping responses (Cassano, Perry-Parrish, & Zeman, 2007;Deans, Frydenberg, & Liang, 2012).…”
Section: Influence Of Parent Coping On Childrenmentioning
confidence: 96%